The Development of Learning Media Based on Powtoon in Global Warming Materials for Class XI High School - M. Nor, M. Nor; Zuhdi, Zuhdi; Asbiah, Asbiah (FKIP-Universitas Riau, 2021)
The learning media developed based on PowToon in global warming material for grade XI students high school. The purpose of this study was to design, analyze the feasibility, and assess the students responses to PowToon based learning media on global warming material. This type of research is a Research and Development (R&D) with the ADDIE model design. The research instrument used was the PowToon media validation assessment sheet which was used by the validator to assess the feasibility of the learning media. Students also filled out a questionnaire to see the responses to the PowToon media developed. The learning media developed after being assessed and given suggestions by the validator are said to be feasible with the valid category. Based on the research results, it was obtained that the average validation of the four media aspects was 86% with the valid category. The average validation of content aspects, design aspects, pedagogical aspects, and ease aspects in media use. As for the results of filling out the student questionnaire, the overall average was 83% with a good category. Where the average questionnaire motivation, learning outcomes, and scientific attitudes. Thus learning media based on PowToon is declared feasible with the valid category used as a learning media.